On the statistical modelling of robot manipulators - Galhano, Alexandra (2019)
A novel approach to the modelling of robot manipulators is presented. Usually, system descriptions are based on a set of differential equations which, due to their nature, lead to very precise results and strategies but, in general, require laborious computations. This motivates the need of alternative methods based on other mathematical concepts. The proposed statistical model gives clear guidelines towards the optimization of the robot performances.